Exploring English Novice Teachers’ Identity Transformation Influenced by Community of Practice - Agnes Riska Pravita; Paulus Kuswandono (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2021)
Research studies have acknowledged the roles of constructing teachers’ identity in early stage for novice teachers. Before entering the real context, novice teachers have formed their professional identity based on their experiences. However, due to the reality shock and different cultural context, transforming into professional identity stage can pose enormous challenge. The challenge has become more serious as the efforts are not supported by sufficient studies and references focusing on the contribution of Community of Practice (CoP) to their identity transformation in Indonesia. Thus, this study aims to explore the English novice teachers’ identity transformation and contribution of CoP to their identity transformation. This research employed a qualitative study. Imagined and practiced identity transformation theory and CoP theory were used to gather the data by conducting interview to three English novice teachers having been teaching for less than two years. The researcher employed selective coding in analyzing the data. It was found that the three participants transformed their imagined identity into practiced identity and CoP contributed to their identity transformation. Thus, teacher education program should prepare student teachers by exposing them to the real context. Further, the schools are urged to set regulations and habits to facilitate novice teachers to adapt with the new social context.